2017
DOI: 10.1186/s40510-017-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cephalometric study on upper airway spaces in different facial types

Abstract: BackgroundCraniofacial growth pattern has been correlated with variations in size of the upper airway spaces. The objective of this study was to evaluate the nasopharyngeal, oropharyngeal, and hypopharyngeal airway spaces variations according to the craniofacial growth pattern, by comparing brachyfacial, mesofacial, and dolichofacial in Angle Class I individuals.MethodsTo measure the spaces, 45 lateral teleradiographs were used and divided into 3 groups per the craniofacial growth pattern, determined by the Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
0
20
0
10
Order By: Relevance
“…16 The relationships between the maxilla and the mandible's sagittal, vertical, and transversal positions have a major impact on the pharyngeal airway, and the craniofacial skeletal pattern also affects the upper airway's dimensions. 17 The literature offers no consensus on how different craniofacial structures affect the airway-although the jaws have a vertical growth pattern, and maxillary retrognathia is often associated with an upper airway obstruction. The available studies' different results may relate to airway dimensions' effects on many different conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The relationships between the maxilla and the mandible's sagittal, vertical, and transversal positions have a major impact on the pharyngeal airway, and the craniofacial skeletal pattern also affects the upper airway's dimensions. 17 The literature offers no consensus on how different craniofacial structures affect the airway-although the jaws have a vertical growth pattern, and maxillary retrognathia is often associated with an upper airway obstruction. The available studies' different results may relate to airway dimensions' effects on many different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on a power analysis using G* Power analysis (G* Power Ver.3.0.10, Kiel, Germany) for superior airway space at an alpha error probability of 0.05 and a power of 90%. 17 The power analysis showed that, at minimum, 32 individuals were required for each subgroup. In order to increase the study’s power, the authors included more individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Sprenger et al . [ 11 ] in their study evaluated hypopharyngeal, oropharyngeal, and nasopharyngeal airway space and found that in oropharynx region, posterior-palatal space measurement was decreased in individuals with a dolichofacial pattern. A total of 28 points were considered with the help of tweed cephalometry angular measurements such as FMA and Y-axis.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on a power analysis using G* Power analysis (G* Power Ver.3.0.10, Kiel, Germany) for superior airway space at alpha error probability of 0.05 and a power of 80% (20). The power analysis showed that a minimum of 21 individuals was required for each subgroup.…”
Section: Methodsmentioning
confidence: 99%